Successful treatment of infantile hepatic hemangioma with high-output heart failure: report of 3 cases and literature review - YANG Jian; DAI Xiaoke; ZHANG Mingman (陆军军医大学学报)
Objective To summarize the clinical characteristics, treatment regimen and clinical outcomes of infantile hepatic hemangioma (IHH) with high-output heart failure (HHF). Methods A retrospective analysis was conducted on 3 IHH infants with concomitant HHF admitted to the Children's Hospital of Chongqing Medical University during October 2020 and October 2023. The characteristics, treatment plans and efficacy were analyzed in the 3 cases. CNKI, WANFANG DATA, Chinese Medical Association Journal Full-text Database, and PubMed databases were retrieved to search domestic and foreign literature concerning the diseases, and the enrolled cases were analyzed and reviewed. Results Among the 3 infants, they were 1 male and 2 females, and aged 1 d, 19 d and 80 d, respectively. The main clinical symptoms were dyspnea and respiratory distress. All 3 patients rapidly progressed to respiratory failure, pulmonary hypertension and heart failure after admission. Diffuse IHH was diagnosed in 2 cases and focal IHH in 1 case. One case of diffuse IHH underwent percutaneous hepatic artery embolization, and the cardiopulmonary function recovered on the day of surgery, and the ventilator was removed. In the other 2 cases, propranolol combined with steroid medication was used, and the estimated right ventricular systolic pressure and E wave to A wave mitral flow ratio (E/A) were the most sensitive indicators in echocardiographic monitoring. There were 24 cases included in literature review, with 4 cases of treatment failure and death, 3 cases of remission, and 17 cases of complete recovery. Conclusion Propranolol combined with steroid medication and percutaneous hepatic artery embolization are effective in treating IHH complicated with HHF. Right ventricular systolic pressure and E/A during drug therapy might be early sensitive marker for the early evaluation of potential therapeutic effects of drugs.